Juan Peron and the Reshaping of Argentina. - Turner, Frederick (Pitt Latin American series., 1983)
Although Juan Perón changed the course of modern Argentine history, scholars have often interpreted him in terms of their own ideologies and interests, rather than seeing the effect of this man and his movement had on the Argentine people. These essays seek to uncover the man behind the myth, to define the true nature of Perónism.